Income Tax in Iraq and the Treatment of Married Women in Charge (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Iraqi legislator taxation  married women in charge of the income tax treatment of the man in charge of tax and the application of the principle of equality of individuals to bear public burdens. The factor legislator women in charge of special treatment in some cases, taking into account the circumstances family allow  tax in the case of whether she was married to a man is unable to completely work and does not have a resource, as well as giving the legislator allow for her children. it observed that the amount of allowing still little is notcommensurate with the high cost of living in addition to limiting the tax allowances granted within the limits of the taxpayer and his immediate family did not take the legislator in charge of the case to support their parents or anyone else to be in charge of her household responsibility religiously.